Control of storage insects as a means of limiting yam tuber fungal rots - Morse, S.; Acholo, M.; McNamara, N.; Oliver, Richard (2000)
Yam rots caused by fungal pathogens (mostly Fusarium spp.) are a major cause of storage losses, and previous work has shown that fungal lesions were only found if there was pre-existing physical damage to the tuber. The general perception is that damage inflicted in the field prior to storage is far more important in this regard than damage caused during storage, and this has led to much research directed at the minimisation of field damage with relatively little work on the amelioration of insect damage during storage. This study examined whether insect damage inflicted on yam tubers during storage in specialised barns is an important agent in the incidence of fungal disease. It was found that treatment of tubers with insecticide dust (Actellic 2% Dust; ai=pirimiphos-methyl) significantly reduced fungal infections resulting from insect attack during storage. In addition, physical damage acquired during harvest appeared to be ameliorated by the insecticide, resulting in significantly fewer fungal lesions. The results suggest that insecticide treatment of yam tubers prior to storage could provide a relatively cheap and effective means of preservation.